ANALISIS PENERAPAN BAGI HASIL PETANI PENGGARAP PADI MELALUI AKAD MUZAROAH (Studi Pada Petani Penggarap Padi Desa Tlogoboyo Kecamatan Bonang Kabupaten Demak) - Niswah, Illiyatun (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2024)
Agriculture is the main commodity in the Indonesian economic sector. Muzaro'ah is the practice of landowners and cultivators working together for what they want, where the landowner hands over his land to cultivators to manage so as to obtain maximum yields. The profit-sharing cooperation carried out in Tlogoboyo Village has the principle of trust as the basis for the agreement without witnesses accompanying it and there is no legal entity to protect it. This study aims to find out how the agricultural system exists in Tlogoboyo Village, the things that underlie the occurrence of profit sharing and what is the Islamic view of the muzaro'ah profit sharing farming system in Tlogoboyo Village, Bonang District, Demak Regency This writing uses a qualitative research design with a type of case study with a descriptive approach. This is because with this type of research, the writer will be able to obtain more accurate information on the research topic. Research methods through observation, interviews and document review. In this study it can be seen that cultivators prefer muzaro'ah profit sharing rather than renting or buying land because the muzaro'ah system is considered more profitable because cultivators are not charged with the cost of renting land and things that include additional costs in carrying out farming activities .